The Impact of A Self-Education Mobile Application (Hd-Sema) on Quality of Life Among Hemodialysis Patients - Nurdina, Gina; Hidayat, Wina Yulia Nazwa; Yuliyawati, Ratna (Universitas Pendidikan Indonesia, 2025)
Introduction: Quality of life is an essential aspect in assessing the management of hemodialysis (HD) patients' overall well-being. Therefore, researchers developed a mobile application called HD-SEMA (Hemodialysis Self Education Management). HD-SEMA application is designed to provide health information and guidance regarding self-management in HD patients. Objective: Researchers are interested in conducting research aimed at finding out the influence of the HD-SEMA mobile application on the quality of life of HD patients. Methods: A quasi-experimental two-group pretest-posttest design with repeated measures was employed. The study was conducted in West Java with 60 participants (30 intervention, 30 control). The intervention group used the HD-SEMA application for four weeks, with sessions conducted twice per week (30–40 minutes each). The control group received standard hospital education. Quality of life was measured using the KDQoL-SF36. Results: Description of Quality of Live in the pre-test intervention group with a mean value of 45.81 and SD 9.33 and post-test 50.03 and SD 8.24. The quality of Live identification results in the intervention group is between the average score of the pre-test and post-test with a value of t=-9.16 and a significance value of 0.000. the mean difference value is 4.22, and the significance value is 0.000. This value shows the difference between the average self-management score of the intervention group and the control group. Conclusions: IT-based intervention is the proper intervention to increase knowledge in self-management in CKD patients so that the patient's quality of life also improves. HD-SEMA also helps patients assess their progress over time by tracking changes in health parameters and disease progression. This evaluation allows patients to evaluate the effectiveness of their treatment and make necessary changes.